Young People and Politics in the UK - Marsh, D. author. aut Link
VIII, 246 p.
Keywords: This book examines how young people understand and live politics, using innovative research methods. It treats age, class, gender and ethnicity as political 'lived experiences'. It concludes that young people are alienated, rather than apathetic, and that their interests and concerns are rarely addressed within mainstream political institutions.